2021
DOI: 10.7759/cureus.18577
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Weight Stigma: Prevalence and Association With Psychiatric Disorder Among Overweight and Obese Individuals

Abstract: Background and objectiveUnlike weight stigma, internalized weight stigma (IWS) may be a common but still underreported problem. With the recent emergence of studies investigating its various aspects in Arab-speaking countries, there is still scant data on its incidence and severity in the literature. In light of this, the aim of this study was to evaluate the prevalence of IWS and its association with psychiatric disorders and sociodemographic factors among overweight and obese individuals in a sample from a S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
5
7
0
Order By: Relevance
“…In addition, our results also show a pattern of sociodemographic characteristics among postpartum women in China who internalize weight bias. Similar to previous studies [ 33 , 35 , 41 , 42 ], our study found BMI to be positively associated with WBI. WBIS scores were higher in overweight (M = 30.57) and obese (M = 31.75) postpartum women compared to those who were underweight (M = 15.83) or normal weight (M = 23.30).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, our results also show a pattern of sociodemographic characteristics among postpartum women in China who internalize weight bias. Similar to previous studies [ 33 , 35 , 41 , 42 ], our study found BMI to be positively associated with WBI. WBIS scores were higher in overweight (M = 30.57) and obese (M = 31.75) postpartum women compared to those who were underweight (M = 15.83) or normal weight (M = 23.30).…”
Section: Discussionsupporting
confidence: 91%
“…Our study included postpartum women in all BMI categories (range = 15.82–34.45 kg/m 2 ), whereas the US study included only two BMI categories of obese or overweight (range = 25.4–62 kg/m 2 ). A study conducted with 868 young adults in Saudi Arabia suggested that those with higher WBI levels were individuals with a higher BMI [ 35 ]. Although lower than the WBI average score in the above studies [ 20 ], the prevalence of a mean level WBI in our study (66.1%) was higher than the results of previous studies for all weight range populations (USA: 44–57%; Saudi Arabia: 46.4%) and higher than the prevalence observed in studies for overweight and obese groups (Saudi Arabia: 57%) compared to other adult populations [ 4 , 5 , 6 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score in the WSSQ indicates a higher level of weight-related self-stigma. Moreover, a total score of the WSSQ 12 items larger than 41 can be viewed as a high level of WRSS [ 41 ]. The Chinese version of the WSSQ had excellent internal consistency in the current study (Cronbach’s α = 0.93) and previous research (Cronbach’s α = 0.88) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…WBI is related to depression, anxiety, body image, and self-esteem [4,18,19], and contributes to disordered eating in adults [17,[20][21][22][23] with any body weight status, including underweight/average weight, overweight, obese [24], and also in children [25]. Such disordered eating would result in increased risk of metabolic syndrome [18] and di culty maintaining a moderate weight [14,26].…”
Section: Introductionmentioning
confidence: 99%